2021
DOI: 10.31234/osf.io/7rxp9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Person-environment fit in the context of sports and its association with subjective well-being

Abstract: Physical activity and sports participation are positively related to physical and mental health as well as to subjective well-being. Various approaches have been used to explain these associations. In our study, we propose that person-environment fit can partly explain the association between sports and subjective well-being. We examined to what extent the fit between an athlete’s individual personality trait levels and the typical personality trait levels of athletes in their sports discipline (supplementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Chan et al (2018) reported that the association between physical activity and well-being was stronger for participants high in Extraversion and Openness but unrelated to other Big Five traits. A recent cross-sectional study showed no effects of congruence between people’s personality traits and the type of sports they perform in the prediction of well-being (Terwiel et al, 2021). Węziak-Białowolska et al (2019) reported in a longitudinal panel study that the well-being benefits of participation in cultural events depended partly on Neuroticism and Extraversion but unexpectedly not on Openness.…”
Section: Conceptualizing Leisure Activitiesmentioning
confidence: 99%
“…Chan et al (2018) reported that the association between physical activity and well-being was stronger for participants high in Extraversion and Openness but unrelated to other Big Five traits. A recent cross-sectional study showed no effects of congruence between people’s personality traits and the type of sports they perform in the prediction of well-being (Terwiel et al, 2021). Węziak-Białowolska et al (2019) reported in a longitudinal panel study that the well-being benefits of participation in cultural events depended partly on Neuroticism and Extraversion but unexpectedly not on Openness.…”
Section: Conceptualizing Leisure Activitiesmentioning
confidence: 99%
“…Chan et al (2018) reported that the association between physical activity and well-being was stronger for participants high in Extraversion and Openness but unrelated to other Big Five traits. A recent cross-sectional study showed no effects of congruence between people's personality traits and the type of sports they perform in the prediction of well-being (Terwiel et al, 2021). Węziak-Białowolska et al (2019) reported in a longitudinal panel study that the wellbeing benefits of participation in cultural events depended partly on Neuroticism and Extraversion but unexpectedly not on Openness.…”
Section: Personality Trait × Leisure Activity Interactionsmentioning
confidence: 97%